2021
DOI: 10.3390/nu13093247
|View full text |Cite
|
Sign up to set email alerts
|

Modifications in the Intestinal Functionality, Morphology and Microbiome Following Intra-Amniotic Administration (Gallus gallus) of Grape (Vitis vinifera) Stilbenes (Resveratrol and Pterostilbene)

Abstract: This efficacy trial evaluated the effects of two polyphenolic stilbenes, resveratrol and pterostilbene, mostly found in grapes, on the brush border membrane functionality, morphology and gut microbiome. This study applied the validated Gallus gallus intra-amniotic approach to investigate the effects of stilbene administration versus the controls. Three treatment groups (5% resveratrol; 5% pterostilbene; and synergistic: 4.75% resveratrol and 0.25% pterostilbene) and three controls (18 MΩ H2O; no injection; 5% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 75 publications
0
17
0
Order By: Relevance
“…Therefore, the administration of NRCl and its derivatives triggers altered expression of key BBM genes involved in digestion, and absorption, with additional effects on intestinal microbiota composition and function. Further and as was previously suggested, these functional changes, as demonstrated via gene expression of key BBM proteins (zinc transporter, inflammatory cytokines, absorptive proteins, and mucin), were previously associated with BBM tissue physiological and morphometric alterations, as increased villi size [ 24 , 50 , 93 , 94 , 95 , 96 , 97 ]. These alterations may potentially also be associated with increased proliferation of cellular populations that hold essential roles in BBM function, including, enterocytes, and therefore, increased villus surface area (the intestinal digestive and absorptive surface), and goblet cells (produce and secrete mucus), both number and diameter in intestinal villi and crypt [ 18 , 22 , 24 , 47 , 50 , 93 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 ].…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Therefore, the administration of NRCl and its derivatives triggers altered expression of key BBM genes involved in digestion, and absorption, with additional effects on intestinal microbiota composition and function. Further and as was previously suggested, these functional changes, as demonstrated via gene expression of key BBM proteins (zinc transporter, inflammatory cytokines, absorptive proteins, and mucin), were previously associated with BBM tissue physiological and morphometric alterations, as increased villi size [ 24 , 50 , 93 , 94 , 95 , 96 , 97 ]. These alterations may potentially also be associated with increased proliferation of cellular populations that hold essential roles in BBM function, including, enterocytes, and therefore, increased villus surface area (the intestinal digestive and absorptive surface), and goblet cells (produce and secrete mucus), both number and diameter in intestinal villi and crypt [ 18 , 22 , 24 , 47 , 50 , 93 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 ].…”
Section: Discussionmentioning
confidence: 56%
“…Previous studies have demonstrated that the intra-amniotic administration of polyphenols and other dietary substances (as soluble fiber extracts) has affected BBM functionality through alterations in gene expression of key BBM digestive and absorptive proteins [ 29 , 45 , 47 , 50 , 77 , 78 ]. In the current study, we investigated the effects of NRCl and its derivatives on BBM gene expression ( Figure 9 ), and the results demonstrated that NRCl, NRTBCl, and NRTOCl increased the expression of ZnT1 and MUC2 and decreased the expression of IL-6.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the significant upregulation of iron transporter gene, ferroportin (at 10% CFWE), is correlated to the reduced Hb levels observed here. Previous studies have shown that the reduced expression of ferroportin is associated with iron sufficiency [ 35 , 58 ]. We hypothesize that kaempferols and quercetin found in CFWE have resulted in the poorer iron physiological status observed here.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the above considerations, we hypothesized that in ovo injection of B. subtilis , raffinose, and their synbiotics would improve the performance and overall health status of broiler chickens at 21 days of age. Therefore, by using the Gallus gallus in vivo model ( 7 , 25 ), the current study was conducted to evaluate the effect of in ovo inoculation with different levels of probiotic ( B. subtilis PB6), prebiotic (raffinose), and their combinations on growth performance, cecal microbial population, cecal volatile fatty acid (VFA) concentration, ileal histomorphology, and ileal gene expression.…”
Section: Introductionmentioning
confidence: 99%